Coupling between the photoactivity and CO2 adsorption on rapidly thermal hydrogenated vs. conventionally annealed copper oxides deposited on TiO2 nanotubes - Lipińska, Wiktoria; Grochowska, Katarzyna; Ryl, Jacek; Karczewski, Jakub; Sawczak, Miroslaw; Coy, Emerson; Mauritz, Vincent; Crisp, Ryan; Siuzdak, Katarzyna (Journal of Materials Science, 2024)
Highly ordered spaced titanium dioxide nanotubes were fabricated via electrochemical anodization and modified with titania nanoparticles and copper oxides. Such materials were rapidly annealed in hydrogen atmosphere or conventionally in a tube furnace in air, in which the temperature slowly increases. Applied synthesis procedure can be considered as simple, cost-effective, and environmentally friendly as it allows for reduction in used materials and enhances sustainable engineering. Manipulating the chemical composition of materials by different thermal treatments resulted in various photoelectrochemical activities and density of CO2 adsorption sites. Rapidly annealed nanotubes decorated by copper oxides exhibit excellent electrochemical properties where one electrode combines both: solar to electricity conversion (photocurrent under visible light 30 µA/cm2) and CO2 adsorption systems (18 times higher current after CO2 saturation). Rapidly thermal hydrogenated TiO2 nanotubes with copper oxides had 17 times higher photocurrent and wider absorption band (380–780 nm) than conventionally annealed ones. Furthermore, the crystal planes such as Cu (111), Cu (220), Cu2O (110), CuO (002) and Cu0, Cu+, Cu2+ oxidation states, and oxygen vacancies were recognized for hydrogenated sample. It should be highlighted that thermal annealing conditions significantly affects ability of copper oxide to CO2 adsorption and CO2 reduction reaction for hydrogenated electrode.<br